FDI sectorial diversification: the trade-transport-tourism nexus - Ana Arias Urones; Ashraf Ali Mahate (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
This Perspective explores the importance of attracting FDI in trade, transport and tourism for improving GDP growth. The successful experiences of Hong Kong, Singapore and Dubai in benefiting from that nexus can be transferred to other small economies to assist them in capitalizing upon that connection.
Keywords: 330